The development of Teacher Academic Emotions (TAE) Scale - Masoud Geramipour; Mehdi Shariatmadari; Somayeh Mahdi (Journal of Pedagogical Research, 2019)
The purpose of this study was to design a comprehensive and native scale, and to investigate the validity and reliability of teachers' academic emotions scale including anxiety, happiness, anger, pride, hope and despair, exhaustion, shame and guilt through a nine-factors TAE model (second order hierarchy) and a two-factors TAE model (third-order hierarchy). A sample of 114 teachers was obtained from the population through multistage random sampling. Considering the questionnaire items and sample size, Partial Least Square Structural Equation Modeling (SEM-PLS) method was used to analyze the data of the questionnaire. Reliability was measured by three criteria: Cronbach alpha, composite reliability (CR), and consistency and validity of the questionnaire by two convergent and divergent validity criteria. Findings indicate that the reliability and validity of all dimensions were acceptable. Standardized coefficients and significance coefficients (t values) indicate the effect of specific structures in that path on each other are significant, and subsequently, the research hypotheses are confirmed. Furthermore, the contribution of R2 values in all dimensions was evaluated moderate to high in measuring all teachers 'emotions. The CVRed and CVCom coefficients indicate that the quality of the internal model and the external model are higher than average and according to GOF, the predictive value is generally much higher than strong, and this TAE model has a prediction power up to 97% of the covariance based models. Finally, in order to compare two models of second order and third order hierarchical TAE, the goodness of fit information measures were evaluated and the second-order hierarchical model was considered a better model for TAE.